Masyarakat Inklusif Berbasis Nilai Budaya dan Norma Sosial di Desa Lakawali Kabupaten Luwu Timur - Ahmad Hidayat; Andi Ima Kesuma; Abdul Rahman A. Sakka (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
This research explores the importance of an inclusive society based on cultural values and social norms in the era of globalization. In an inclusive culture, everyone is recognized, regardless of background or identity, with equal opportunities to participate and contribute. This creates an equitable environment, enriches cultural diversity, and strengthens the nation's collective identity. A.R Radcliffe Brown's functional, structuraltheory is used to see culture as an adaptive mechanism for orderly social life. This research is descriptive and qualitative in nature, using observation, interviews, anddocumentation methods. Source triangulation is used to ensure the validity of the data.Data were analyzed in the context of inclusive society theory based on cultural values andsocial norms. The research results in Lakawali Village, East Luwu Regency, show thatcultural values and social norms encourage acceptance of diversity, openness, andtolerance in society and function as protection against the digital era.Keywords :Inclusive Society, Cultural Values, Social Norms